2018
DOI: 10.1088/1748-9326/aabef0
|View full text |Cite
|
Sign up to set email alerts
|

Spatial optimization for decentralized non-potable water reuse

Abstract: Decentralization has the potential to reduce the scale of the piped distribution network needed to enable non-potable water reuse (NPR) in urban areas by producing recycled water closer to its point of use. However, tradeoffs exist between the economies of scale of treatment facilities and the size of the conveyance infrastructure, including energy for upgradient distribution of recycled water. To adequately capture the impacts from distribution pipes and pumping requirements, site-specific conditions must be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…Costs for water distribution and wastewater collection in the municipal and manufacturing sectors are estimated based on average cost data compiled by the World Health Organization [38], combined with the modeled withdrawal and returnflow volumes (supplementary information, section S1.3). This approach aligns closely with previous work that quantified costs to achieve universal access to clean water and sanitation [38,41,42], but also smooths out some of the known cost variability for distribution systems under diverse topographic conditions [43], and thus results do not provide detailed cost-level information at the municipal-or city-scale.…”
Section: Methodssupporting
confidence: 70%
“…Costs for water distribution and wastewater collection in the municipal and manufacturing sectors are estimated based on average cost data compiled by the World Health Organization [38], combined with the modeled withdrawal and returnflow volumes (supplementary information, section S1.3). This approach aligns closely with previous work that quantified costs to achieve universal access to clean water and sanitation [38,41,42], but also smooths out some of the known cost variability for distribution systems under diverse topographic conditions [43], and thus results do not provide detailed cost-level information at the municipal-or city-scale.…”
Section: Methodssupporting
confidence: 70%
“…Engström et al 42 Guo et al 38 Kavvada et al 28 Lafortezza et al 41 Liu et al 39 Wu et al 40 Market system flexibility in real-time i. Incentives for water efficiency solutions that enable automated response to electricity pricing ii.…”
Section: Save Water At End-use To Avoid Embodied Energy and Materialsmentioning
confidence: 99%
“…For example, industrial processing, power plant cooling, and park/garden irrigation can be supported with urban wastewater 17,27 . Pumping distances and GHG impacts are minimized by focusing on applications located within the same building, industry, or neighborhood 28 . In the reverse direction, the expansion of distributed low-carbon thermal power generation in response to the Paris Agreement has the potential to create a new source of waste heat.…”
Section: Save Water At End-use To Avoid Embodied Energy and Materialsmentioning
confidence: 99%
“…The influence of treatment system capacity, degree of decentralization and treatment system technology has been evaluated using life cycle assessment (LCA) [23][24][25], LCA and life cycle cost assessment (LCCA) [26] and QMRA [10]. Both Cashman et al [26] and Kavvada et al [24,25] found that design flow or capacity economies of scale strongly influenced cost and environmental performance of decentralized membrane bioreactors (MBRs), with clear advantages for larger systems. However, they only evaluated larger, community-scale NPR systems, which have different distribution and collection requirements and pathogen risk profiles than single building systems.…”
Section: Introductionmentioning
confidence: 99%